Research on yaw moment control system for race cars using drive and brake torques - Kobayashi, Ikkei; Kuroda, Jumpei; Uchino, Daigo; Ogawa, Kazuki; Ikeda, Keigo; Kato, Taro; Endo, Ayato; Peeie, Mohamad Heerwan; Narita, Takayoshi; Kato, Hideaki (MDPI, 2023)
The yaw acceleration required for circuit driving is determined by the time variation of the yaw rate due to two factors : corner radius and velocity at the center of gravity. Torque vectoring systems have the advantage where the yaw moment can be changed only by the longitudinal force without changing the lateral force of the tires, which greatly affects lateral acceleration. This is expected to improve the both the spinning performance and the orbital performance, which are usually in a trade-off relationship. In this study, we proposed a yaw moment control technology that actively utilized a power unit with a brake system, which was easy to implement in a system, and compared the performance of vehicles equipped with and without the proposed system using the Milliken Research Associates moment method for quasi-steady-state analysis. The performances of lateral acceleration and yaw moment were verified using the same method, and a variable corner radius simulation for circuit driving was used to compare time and performance. The results showed the effectiveness of the proposed system.